The Application of Leech’s Politeness Maxims in Shakespeare’s The Merchant of Venice - Eshreteh, Mahmood K. M.; Badran, Huda (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2020)
This study aims to investigate Shakespeare’s The Merchant of Venice in light of the application of Leech’s politeness maxims. The study uses a qualitative method in analyzing the utterances of the major characters in the play; Shylock, Antonio and Bassanio, since most of the events within the play focus on their demands, personalities and behaviors. The purpose of this study is to reveal the degree of politeness reflected in the characters’ speeches. 17 extracts from Act 1 scene 3 (a street in Venice) and 6 extracts from Act 4 scene 1 (the court scene) are explored due to their importance in the plot development. In light of the analysis, some of the factors are highlighted according to their significant role in determining the use of politeness or impoliteness strategies. These factors are power, psychological aspects, personal values, irony principle, social status and religion. The study also examines the way in which the six maxims are employed in the extracts. To conclude, politeness strategies can be used to reveal much about people’s identities, values and psychology.